Does liquidity matter? Properties of a synthetic divisia monetary aggregate in the euro area - Livio Stracca (European Central Bank (ECB), 2001)
This paper sets out to build a synthetic quarterly Divisia monetary aggregate for the euro area using area wide data over the sample period from 1980 to 2000. Then, the analysis proceeds in two separate steps. First, the demand for this Divisia monetary aggregate is evaluated using econometric techniques. By means of a cointegrated VECM model, a theoretically plausible and stable demand function may be estimated. Second, the information content of the Divisia monetary aggregate as regards future output and inflation in the euro area is analysed. The outcome of this analysis suggests that the Divisia monetary aggregate has some information content from a forward-looking perspective, of comparable quality as simple sum M1 and M3. More in general, the paper lends further support to the view that money and 'liquidity' should be assigned an important role in shaping monetary policy in the euro area.
Keywords: E41; E52; 330; Divisia monetary aggregates; EMU; liquidity; Money demand